2021
DOI: 10.52229/ajahs.v5i3.783
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Iron Deficiency Anemia Among Pregnant Females Visiting Tertiary Care Hospitals, Lahore

Abstract: Iron deficiency anemia refers to the anemia caused by insufficient iron stores within the body. The main cause of anemia in obstetrics is iron deficiency, which has a worldwide prevalence estimated between 20%–80% and constitutes mainly female population.  Objective: To find out the determinants of iron deficiency anemia amongst pregnant women visiting Tertiary Care Hospitals, Lahore. Methods: A cross-sectional study was conducted at Sir Ganga Ram Hospital, Lahore. A sample of 245 pregnant female patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Ullah et al printed that 57.7% of women are anemic in Lahore [23]. In the latest research of 2020, it is reported that many socioeconomic factors are pivotal in developing anemia among pregnant women of Lahore [24]. In the current study, we found an overall prevalence of 49.5 % in pregnant women.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Ullah et al printed that 57.7% of women are anemic in Lahore [23]. In the latest research of 2020, it is reported that many socioeconomic factors are pivotal in developing anemia among pregnant women of Lahore [24]. In the current study, we found an overall prevalence of 49.5 % in pregnant women.…”
Section: Discussionsupporting
confidence: 57%
“…There have been few studies aimed to look at maternal anemia with women in the third trimester of pregnancy [20,21]. According to a report, there are about 89% of pregnant women are anemic in rural areas of Punjab while the prevalence of anemia in Lahore is high [22][23][24][25]. One of our study groups belongs to the Walled City of Lahore and the other from the new City of the Lahore.…”
Section: Introductionmentioning
confidence: 99%